# If x = 1- 3t and y = 2t – 1…

# Solution:

We are given x = 1 – 3t and y = 2t – 1, and we need to determine the value for t when x = y. We should notice that both x and y are already in terms of t. Thus, we can substitute 1 – 3t for x and 2t – 1 for y in the equation x = y. This gives us:

1 – 3t = 2t – 1

2 = 5t

2/5 = t

**Answer: D**

#### About The Author

Scott Woodbury-Stewart is the founder & CEO of Target Test Prep. A passionate teacher who is deeply invested in the success of his students, Scott began his career teaching physics, chemistry, math, and biology. Since then, he has spent more than a decade helping students gain entry into the world’s top business schools, logging 10,000+ hours of GMAT instruction. Scott also served as lead content developer and curriculum architect for the revolutionary quant course Target Test Prep GMAT Quant.